LAYANAN KONSELING ISLAMI DALAM MEMBINA KESIAPAN MENIKAH PADA SISWA SMK BROADCASTING BINA CREATIVE MEDAN - Safura Afni (Al-Mursyid : Jurnal Ikatan Alumni Bimbingan dan Konseling Islam (IKABKI), 2020)
This research was conducted at the BBC Medan Vocational School, while the aim was to find out the implementation of Islamic counseling services in the BBC Medan Vocational School. To find out the application of Islamic counseling services in fostering marriage readiness at BBC Medan Vocational students. The subject of this study is the BK teacher who has made various efforts relating to the expectations of Islamic Counseling Services in fostering the readiness of marriage to BBC Medan Vocational School students. This research uses descriptive qualitative research. Data collection techniques in this study used direct observation or observation, interviews and documentation of BK teachers in implementing Islamic counseling services in fostering the readiness of marriage to BBC Medan Vocational School students. Presentation of data uses three stages of the process, namely data reduction, data presentation, and drawing conclusions.The results of this study illustrate that the implementation of Islamic counseling services at SMK BBC Medan has been going well, only BK teachers adjust to the circumstances and needs of students. Through the implementation of group guidance services conducted by counseling guidance teachers with marriage readiness material to students, these students understand the purpose and benefits of the material delivered for the future to be even better, not only that the efforts made by guidance and counseling teachers in implement group guidance services to anticipate and prevent negative things from happening to these students, each individual will get married and this is an important material as a provision for the future of students especially those who sit in class XII SMK BBC Medan in order to realize sakinnah mawaddah warahamah family is like the teachings of Rasullah SAW.Keyword : Counseling Teacher, Application of islami counseling services